Earthquakes in the Tibet Region and Their Socioeconomic Impacts - Mehtab, Muhammad (Prevention and Treatment of Natural Disasters, 2023)
Tibet is the southernmost province of China and is one of the most seismically active areas in the world, experiencing regular earthquakes due to the collision of the Indian and Eurasian tectonic plates. These seismic activities not only affect the unique geological landscape but also have deep socioeconomic impacts. This article gives a comprehensive account of the multifaceted effects of earthquakes in Tibet, extending from immediate destruction of infrastructure, loss of precious lives, and environmental damage to long-term challenges such as displacement of people, economic disruption, damage to endangered heritage and public health issues. The remote location of the region in a difficult-to-access part, the traditional structure of society, and reliance on agriculture intensify its vulnerability to seismic risks. Policies for post-earthquake mitigation are crucial to reducing these impacts. This study highlights the importance of earthquake-resistant infrastructure, community-driven disaster preparedness, early alerts and warning systems, and efficient governmental measures. Moreover, the preservation of cultural heritage and international cooperation are key for sustainable recovery. By investigating the complex interconnection of geophysical forces and human activities, this article provides insights into effective disaster management and long-term recovery strategies in the seismically active and culturally rich Tibet region.